Acute toxicity effects of perfluorooctane sulfonate on sperm vitality, kinematics and fertilization success in zebrafish - 夏继刚 牛翠娟 (Chinese journal of oceanology and limnology, 2017)
Perfluorooctane sulfonate （PFOS） has emerged as one of the most concerning contaminants in recent years. This study aimed to investigate the acute toxicity effect of PFOS on sperm viability, kinematics and fertilization success in zebrafish （Danio rerio）. Sperm were activated in aqueous media containing a range of PFOS concentrations （0, 0.09, 0.9 and 9 mg/L）. Viabilities and kinematics of the sperm exposed to different PFOS treatments were assessed via computer-assisted sperm analysis （CASA） at 20, 40, 60, and 80 s after activation. PFOS exposure decreased the percentage of motile sperm, the curvilinear velocity （VCL）, and the mean angular displacement （MAD） of spermatozoa, but showed no influence on the straight- line velocity （VSL） or the angular path velocity （VAP）. Furthermore, a significant decrease in fertilization success was observed in spermatozoa that were exposed to 0.9 mg/L PFOS or more. These findings indicate that PFOS pollution in natural aquatic environment may be a potential threaten to successful reproduction of fish.